Simple Model of Herd Behaviour, a Comment - Andrea Morone (Economics and Econometrics Research Institute (EERI), 2008)
In his `Simple model of herd behaviour', Banerjee (1992) shows that – in a sequential game – if the first two players have chosen the same action, all subsequent players will ignore their own information and start a herd, an irreversible one. The points of strength of Banerjee's model are its simplicity and the robustness of its results. Its weakness is that it is based on three tie-breaking assumptions, which according to Banerjee minimise herding probabilities. In this paper we analyse the role played by the tie-breaking assumptions in reaching the equilibrium. Even if the overall probability of herding does not change dramatically, the results obtained, which differ from Banerjee's are the following: players' strategies are parameter dependent; an incorrect herd could be reversed; a correct herd is irreversible. There are, in addition, some several cases where available information allows players to find out which action is correct, and so an irreversible correct herd starts.
Keywords: D8; 330; Herd behaviour